Comportamento de compra por impulso: proposta de um modelo de mensura????o relacional - Cunha, Roberto de Araujo Nascimento (2012)
Impulse buying is characterized as a sudden, energetic and hedonistically complex act. The acquisition of a new product provides to the consumer an hedonic satisfaction that is contrary to rational thinking. Consuming is related not only with the objects that are acquired but also with the interaction with other consumers. In light of that, the focus of this study is to explore how the desire (urgency) influences the trend of impulse buying and also how consumer profile, store environment and self-control strategies influence the desire to buy. A survey was carried out with 1.231 consumers, in early 2012. The target group was restricted to consumers of both genders who had bought clothing and accessories for their own use in the three previous months. Through statistical analyses, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), analyzed with Structural Equation Modeling (SEM) estimated by Partial Least Squares (PLS) using Smart PLS software, we could understand the relationships between desire and impulse buying tendency. The results suggest that desire to buy explains 39.8% of impulse buying tendency. This remained true when types of consumers and product relevance were considered. The consumer profile (represented by normative aspects and happiness) influenced positively and self-control strategies (represented by consequence and financial impact aspects) influenced negatively the desire to buy. The store environment aspects did not influence the desire to buy. These results contribute to the understanding of the impulse buying phenomenon, because it shows that for certain products and consumer profiles, purchase is a hedonistic act. In these cases, the decision is being driven not by tangible attributes and benefits of the product and store environment, but by a need to be socially accepted. Limitations of this study and suggestions for future studies are also discussed.